Role of Electronic Media in Politics of Punjab, Pakistan: A Case Study of Lahore - kamran, M Kamran khan; Dr. Muhammad Shahzad (Journal of Peace, Development and Communication, 2021)
Electronic media had been the most important forum in exchanging different ideas and political awareness, therefore shaping the political opinion and getting change in political steup of Punjab. Researcher aims at measuring how educated people are persuaded by political talk shows about national issues. About 200 respondents of this study were the students belong to Colleges and Universities of Lahore, Pakistan. Purposive and convenient sampling techniques were used for data collection where questionnaires were as a primary tool of data collection. The findings indicated that viewers of talk shows have greater influence on youth and played important role in giving political awareness. Typically most of people showing their great interest and time in watching talk shows during prime time hours. Basic purpose was to identify how electronic media affected the political perception and mobilization among people of Pakistan. The aim was also to measure show talk shows influenced the political perception over different issues. The resutls of the present study were based survey method conducted from people of punjab, which belong to different age groups, gender, education level and profession. Findings revealed a significant correlation among variables. In this research paper the majority of respondents thought that Talk shows guide the people to comprehend political issues and these talk shows are most credible source of information.